Effect of Heat Treatment Parameters on the Modification of Nano Residual Austenite of Low-Carbon Medium-Chromium Steel - Yiran Wang; Ruian Wang; Wenzhen Yu; Yimin Gao (Nanomaterials, 2023)
The ball milling lining board operates in a harsh environment, and the current materials fail to meet the requirements for large-sized boards due to the lack of synergistic properties between impact toughness and wear resistance. To address this issue, a low-carbon medium-chromium steel with martensite and nano residual austenite phases have been designed for future use. However, the residual austenite network could decrease the properties. Heat treatment, which includes processes like quenching and tempering, has the potential to alter the morphology and quantity of nano-scale residual austenite in the steel. In this study, the influence of heat treatment parameters on the morphologies and properties of steel has been investigated to address the wide-ranging fluctuations in impact toughness affected by nano residual austenite. Furthermore, the effect of cooling transformation on the microstructure has also been examined. The research findings indicate that modifying the quenching temperature of the steel within the range of 950–1100 °C results in a microstructure comprising martensite and nano residual austenite. At all quenching temperatures, the hardness exceeds 45 HRC, and the impact toughness shows a consistent improvement with increasing quenching temperature, indicating a modification of the nano residual austenite phase. The failure mode is primarily dimple fracture, with quasi-dissociation fracture as a secondary mode. The optimal heat treatment parameters are annealing at 930 °C, oil quenching at 1050 °C, and tempering at 250 °C. Under this condition, the steel exhibits a hardness of 51 HRC and impact toughness of 40 J/cm2 and an approximate fourfold increase compared to the untreated sample.